STUDY OF THE PHYSICAL-MECHANICAL PROPERTIES OF FOAM -CONCRETE - Turapov Farkhod Khursanovich (American Journals Publishing, 2023)
Foam concrete brands adopted the composition in relation to the amount of Foam concrete cement in the binder: for example: (the rest is mineral additives): Foam concrete -100 (100), Foam concrete -60 (60%), Foam concrete -50 (50), Foam concrete -30 (30%). With the increase of mineral additives, the strength of Foam concrete decreases, however, the strength of Foam concrete-30 is high enough and shows that it is higher than the strength of ordinary portland cement. This can be achieved by mechanochemical activation during dry grinding of Foam concrete components together with superplasticizer.